An analysis on the criterion "Assistance to the economic development of the host state" for realizing the concept of investment contracts under the ICSID Arbitration Convention - Mohammad Javad Abdollahi; Mohammad Karimi (دانشنامه حقوق اقتصادی)
The ICSID Convention in the settlement of investment disputes for several reasons does not provide a definition of investment contracts, which has caused the judicial procedure in many international investment arbitration cases to try to explain the limitations related to the confirmation of investment contracts. In this direction, the criterion "assistance to the economic development of the host government" has been considered as the most controversial criterion among arbitral tribunals. Why this criterion could not be uniformly applied in international arbitration courts and how to prevent its removal in the arbitration procedure is the subject of the analysis presented in this research. The material presented in this research, which was conducted with the method of reading books and survey tools, shows that in facing the With numerous problems related to this standard, it is necessary to pay attention to new investment methods and adopt a flexible approach to fulfill the requirements.